2011
DOI: 10.2478/s11532-011-0027-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment on the phase transition of ZrMo2O8 and photocatalytic activity

Abstract: ZrMo2O7(OH)2·2H2O was obtained from ZrOCl2·2H2O and Na2MoO4·2H2O by a coprecipitation method. The phase and structural changes occurred during the heat-treatment of ZrMo2O7(OH)2·2H2O were investigated by XRD, IR and XPS analysis. The sequence of phase transformation can be divided into three stages: (1) transformation of ZrMo2O7(OH)2·2H2O to orthorhombic LT-ZrMo2O8 up to 300°C; (2) obtaining of mixture of both polymorphs of ZrMo2O8: cubic and trigonal at 400°C; (3) conversion to single trigonal (α) ZrMo2O8 abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…ZrMo 2 O 8 exists in a variety of polymorphic modifications depending on pressure and temperature. At ambient pressure, the thermodynamically stable polymorphs are the trigonal and monoclinic phase, which is stable at high and low temperature, respectively [2,3]. It is noted that ZrMo 2 O 8 has a special metastable phase-cubic structure-which has been proved to be a dual functional material [4].…”
Section: Introductionmentioning
confidence: 98%
“…ZrMo 2 O 8 exists in a variety of polymorphic modifications depending on pressure and temperature. At ambient pressure, the thermodynamically stable polymorphs are the trigonal and monoclinic phase, which is stable at high and low temperature, respectively [2,3]. It is noted that ZrMo 2 O 8 has a special metastable phase-cubic structure-which has been proved to be a dual functional material [4].…”
Section: Introductionmentioning
confidence: 98%
“…ZrMo 2 O 8 has several crystal phases: monoclinic phase (β), trigonal phase (α), cubic phase (γ), orthorhombic phase (LT) and high-pressure phases (monoclinic (δ) and triclinic (ε)). Their conversion is mainly caused by temperature and pressure [56]. The relatively stable crystal phases, under atmospheric pressure, are the α and β crystal phases [43].…”
Section: Introductionmentioning
confidence: 99%
“…•iPrOH as a precursor to form ZrMo 2 O 8 pristine gels, which were later subjected to heat treatment to obtain α-ZrMo 2 O 8 ; Shivanekar and Chudasama[60] used zirconyl chloride octahydrate and ammonium molybdate as raw materials to synthesize ZrMo 2 O 8 for the catalytic decomposition of hydrogen peroxide; Lind et al[54] obtained γ-ZrMo 2 O 8 by calcinating zirconium molybdate precursors for the synthesis of cubicphase zirconium tungstate in the first preparation and characterization of γ-ZrMo 2 O 8 ; Lind et al[58] found that zirconium perchlorate was the most suitable precursor, followed by zirconium nitrate and zirconium chloride, when forming ZrMo 2 O 8 with a rod-shaped structure; Mancheva et al[56] prepared ZrMo 2 O 8 precursors with ZrOCl 2 •2H 2 O and Na 2 MoO 4 •2H 2 O as raw materials using a co-precipitation method, and systematically investigated the phase transition conditions of ZrMo 2 O 8 . ZrMo 2 O 8 also shows advantages in electrochemical detection.…”
mentioning
confidence: 99%